LC–MS/MS Method for Measurement of Thiopurine Nucleotides (TN) in Erythrocytes and Association of TN Concentrations With TPMT Enzyme Activity - Bajaj, Amol O.; Kushnir, Mark M.; Kish-Trier, Erik; Law, Rachel N.; Zuromski, Lauren M.; Molinelli, Alejandro R.; McMillin, Gwendolyn A.; Johnson-Davis, Kamisha L. (Frontiers in Pharmacology, 2022)
Monitoring concentrations of thiopurine metabolites is used clinically to prevent adverse effects in patients on thiopurine drug therapy. We developed a LC–MS/MS method for the quantification of 6-thioguanine (6-TG) and 6-methylmercaptopurine (6-MMP) in red blood cells (RBCs). This method utilizes an automated cell washer for RBC separation from whole blood samples and washing of the separated RBCs. The lower limit of quantification of the method was 0.2 μmol/L for 6-TG (∼50 pmol/8 × 108 RBC) and 4 μmol/L for 6-MMP (∼1,000 pmol/8 × 108 RBC). The total imprecision of the assay was <3.0%. The upper limit of linearity for 6-TG and 6-MMP was 7.5 μmol/L and 150 μmol/L, respectively. The stability of the thiopurine metabolites under pre- and post-analytically relevant conditions was also evaluated. A good agreement was observed between this method and validated LC–MS/MS methods from three laboratories, except for ∼40% low bias for 6-MMP observed in one of the methods. The assessment of the association between 6-TG and 6-MMP concentrations with thiopurine S-methyltransferase (TPMT) phenotype and genotype demonstrated a statistically significant difference in the thiopurine metabolite concentrations between the TPMT groups with normal and intermediate activity of 6-MMP (p < 0.0001), while the difference in 6-TG concentrations was statistically not significant (p = 0.096). Among the samples with normal TPMT activity, higher concentrations of 6-MMP (p = 0.015) were observed in pediatric samples than in the samples of adults. No statistically significant differences were observed in the distributions of 6-TG and 6-MMP concentrations among the evaluated genotypes.